Streptococcus pneumoniae meningitis and the CNS barriers - Gil, Eliza; Wall, Emma; Noursadeghi, Mahdad; Brown, Jeremy S. (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus pneumoniae (SPN) is a globally significant cause of meningitis, the pathophysiology of which involves damage to the brain by both bacterial virulence factors and the host inflammatory response. In most cases of SPN meningitis bacteria translocate from the blood into the central nervous system (CNS). The principal site of SPN translocation into the CNS is not known, with possible portals of entry proposed to be the cerebral or meningeal blood vessels or the choroid plexus. All require SPN to bind to and translocate across the vascular endothelial barrier, and subsequently the basement membrane and perivascular structures, including an additional epithelial barrier in the case of the blood-CSF barrier. The presence of SPN in the CNS is highly inflammatory resulting in marked neutrophilic infiltration. The secretion of toxic inflammatory mediators by activated neutrophils within the CNS damages pathogen and host alike, including the non-replicative neurons which drives morbidity and mortality. As with the translocation of SPN, the recruitment of neutrophils into the CNS in SPN meningitis necessitates the translocation of neutrophils from the circulation across the vascular barrier, a process that is tightly regulated under basal conditions – a feature of the ‘immune specialization’ of the CNS. The brain barriers are therefore central to SPN meningitis, both through a failure to exclude bacteria and maintain CNS sterility, and subsequently through the active recruitment and/or failure to exclude circulating leukocytes. The interactions of SPN with these barriers, barrier inflammatory responses, along with their therapeutic implications, are explored in this review.